ҚАРАҚАЛПАҚ ПРОЗАСЫНДА ГҮРРИҢ ЖАНРЫНДА ДЕТЕКТИВ ФОРМАЛАРДЫҢ БЕРИЛИЎИ - Алламуратова, З. (SCIENCE and SOCIETY, 2023)
The article examines the use of detective forms in the narrative genre in Karakalpak prose. During the period of independence, examples were taken from the works of great writers of Karakalpak literature.
Keywords: literature; genre; detective story; plot; comic plot; story